‘A superb library at bargain cost’: Britain’s Jazz Book Club, 1956–67 - Ainsworth, Alan John (Jazz Research Journal, 2023)
Offering access to low-cost authoritative literature, the Jazz Book Club was a successful and influential venture, publishing 66 subscription titles and 11 occasional volumes between 1956 and 1967. The Club was created to meet the demand for information by the rapidly growing post-war jazz audience in Britain. Extending the intellectual discourse of the 1930s, an educated, socially diverse generation coming to jazz in the 1940s and 1950s was serious about the music and earnest in their pursuit of information. Although the new fans were often fiercely partisan in their preferences, the Club believed its book choices would appeal broadly across the emerging jazz community. Surprisingly, the Jazz Book Club has been little researched. Using previously unexamined archival records and Jazz Book Club publications, contemporary journals and personal recollections alongside recent scholarship, this article provides the first full account of a small but important moment in British jazz history. Drawing on Karl Mannheim’s epistemology of generations, I argue that the Jazz Book Club was created to meet the demands of a young post-war generation for whom jazz assumed an unexampled measure of cultural saliency. The Jazz Book Club’s moment passed as a later generation turned away from jazz after the early 1960s.